Prove that in every commutative ring of characterstic 2 (a+b)^2=a^2+b^2
Answers
Answered by
0
A proof
0=(a+a)^2-(a+a)=(a^2-a)+(a^2-a)+a+a=a+a=0
As to your point regarding commutatively note that R must be commutative
(a+b)^2=a^2+ab+ba+b^2
=(a+b)
ab+ba=0
0=(a+a)^2-(a+a)=(a^2-a)+(a^2-a)+a+a=a+a=0
As to your point regarding commutatively note that R must be commutative
(a+b)^2=a^2+ab+ba+b^2
=(a+b)
ab+ba=0
Similar questions
Math,
9 months ago
Social Sciences,
9 months ago
English,
9 months ago
Social Sciences,
1 year ago
Chemistry,
1 year ago
Chemistry,
1 year ago
English,
1 year ago